Analisis Kinerja Kondensor Destilasi Minyak Atsiri Dengan Bahan Baku Daun Cengkeh Kapsitas 200kg - Zulfahri Mardiansyah; Agus Supraytno; TB.U. Adi Subekhi; Amri Abdulah (Jurnal Teknologika, 2025)
Essential Oil or Essential Oils is a commodity that has great potential in Indonesia, such as the Cosmetics, Foodand Beverage Medicines industry. Therefore, the author analyzes the performance of the essential oil distillation condenserwith a capacity of 200kg with solutions such as flow. Distillation can be done by 3 methods, namely: Distillation with waterand steam / steam distillation system (water and steam distillation), Distillation with boiling system (water distillation /hydro-distillation), and distillation with direct steam (Direct steam distillation / Dry steam). The Reynolds number showsa value of 73.308. Then the type of fluid flow in the pipe is Turbulent Flow. LMTD provides the average rate of heattransferred accurately and quickly which the author has calculated to get a value of 127.61 K. The type of heat exchangeris so complex that it requires a correction factor (Fc) of 1.056 as a comparison of the actual heat transfer rate with themaximum heat transfer rate in the condensing zone of 1.051K.